Connecting and Reconnecting: Outfitting the Figure of the Cyborg for Transnational Coalition-building - Jessica E. Brophy (KOME: An International Journal of Pure Communication Inquiry, 2016)
This work attempts to rehabilitate Donna Haraway’s (1991) figure of the cyborg to increase the possibilities of alliances between transnational feminism and cyborg or technoscience feminism. Haraway’s cyborg offers little impetus for political investment and coalition building. This work develops an optional prosthesis of responseability for the cyborg figuration, one that enables the cyborg to invest locally. This ethic of response-ability is developed via the work of Mary Strine (1989), Adrienne Rich (1984) and Aimee Carillo Rowe (2005). This supplementary ethic grafts a “collectivist conscience” onto the permeable being of the cyborg, encouraging alliance- and coalitionbuilding.